Relief memory consolidation requires protein synthesis within the nucleus accumbens. (June 2016) - Bruning, Johann E.A.; Breitfeld, Tino; Kahl, Evelyn; Bergado-Acosta, Jorge R.; Fendt, Markus
Abstract: Relief learning refers to the association of a stimulus with the relief from an aversive event. The thus-learned relief stimulus then can induce, e.g., an attenuation of the startle response or approach behavior, indicating positive valence. Previous studies revealed that the nucleus accumbens is essential for the acquisition and retrieval of relief memory. Here, we ask whether the nucleus accumbens is also the brain site for consolidation of relief memory into a long-term form. In rats, we blocked local protein synthesis within the nucleus accumbens by local infusions of anisomycin at different time points during a relief conditioning experiment. Accumbal anisomycin injections immediately after the relief conditioning session, but not 4 h later, prevented the consolidation into long-term relief memory. The retention of already consolidated relief memory was not affected by anisomycin injections. This identifies a time window and site for relief memory consolidation. These findings should complement our understanding of the full range of effects of adverse experiences, including cases of their distortion in humans such as post-traumatic stress disorder and/or phobias. Graphical abstract: Injections of the protein synthesis inhibitor anisomycin into the nucleus accumbens block the consolidation of relief memory. Highlights: Relief learning is associating a stimulus with the offset of an aversive event. Local injections of anisomycin were used to block local protein synthesis. Our data show that consolidation of relief memory is protein synthesis dependent. This protein synthesis takes place in the nucleus accumbens. Four hours after conditioning, anisomycin injections were not effective anymore.